1993
DOI: 10.1164/ajrccm/147.6_pt_1.1507
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Alveolar Macrophages Expressing Surface Molecules of the CD11/CD18 Family in Sarcoidosis and Idiopathic Pulmonary Fibrosis Is Related to the Production of Superoxide Anions by These Cells

Abstract: This study was designed to investigate the expression and functional properties of leukocyte adhesion molecules (LeuCAM; CD11/CD18 family) on human alveolar macrophages (AM) from patients with sarcoidosis and idiopathic pulmonary fibrosis. Cells were obtained by bronchoalveolar lavage (BAL) from 17 patients with sarcoidosis (SA), 15 with idiopathic pulmonary fibrosis (IPF), and 14 nonsmokers (NS). Expression of LeuCAM on freshly isolated cells was studied using the peroxidase-antiperoxidase method with monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
3
30
0
2
Order By: Relevance
“…Several investigators have demonstrated that alveolar macrophages isolated from the BAL of sarcoidosis patients possess an enhanced capacity to metabolize oxygen and to produce hydrogen peroxide and superoxide anions, especially under the influence of activating substances [6,[13][14][15][16]. In accordance to these in vitro observed phenomena, the EBC of sarcoidosis patients has elevated levels of 8-isoprostane [8,9], whereas in the present study a systemic redox imbalance was also observed.…”
Section: Discussionsupporting
confidence: 85%
“…Several investigators have demonstrated that alveolar macrophages isolated from the BAL of sarcoidosis patients possess an enhanced capacity to metabolize oxygen and to produce hydrogen peroxide and superoxide anions, especially under the influence of activating substances [6,[13][14][15][16]. In accordance to these in vitro observed phenomena, the EBC of sarcoidosis patients has elevated levels of 8-isoprostane [8,9], whereas in the present study a systemic redox imbalance was also observed.…”
Section: Discussionsupporting
confidence: 85%
“…The fractions of the washing-procedures were pooled and the number of cells removed was counted (MD-Kova Raster 10, Madaus, Köln, FRG). This method allows the generation of BA-cell monolayers consisting mainly of alveolar macrophages [26,27]. In our experiments, macrophage enrichment was >95%.…”
Section: Gsh-oxidation Assay Preparation Of Bronchoalveolar Inflammatmentioning
confidence: 75%
“…BA-cells obtained by BAL were cultured in a standard medium (RPMI 1640, Sigma) using 6-well, flatbottomed, plastic culture dishes (Falcon, NJ, USA) as described previously [10,[24][25][26][27]. After incubation for 30 min at 37°C with 5% CO 2 , non adherent cells were removed by washing five times with Hank's balanced salt solution (HBSS) at 37°C.…”
Section: Gsh-oxidation Assay Preparation Of Bronchoalveolar Inflammatmentioning
confidence: 99%
“…The relative contributions of alveolar macrophages, monocytes and polymorphonuclear neutrophils to the overall respiratory burst in lung inflammatory disorders probably varies for each specific disease [4], as indicated in studies in patients with adult respiratory distress syndrome, sarcoidosis and idiopathic pulmonary fibrosis [5,6,32,37,39] as well as in animal studies, using experimental models of lung injury [40,41]. In conclusion, the present study clearly demonstrates that alveolar macrophages, monocytes and polymorphonuclear neutrophils posess significant differences in potential to increase their intracellular levels of oxidants upon stimulation.…”
Section: Discussionmentioning
confidence: 99%